Anaesthesia and pre‐hospital emergency medicine. (4th December 2012) - Booth, A.; Steel, A.; Klein, J.
Summary: Major trauma is a leading cause of death and disability in the UK, particularly in the young. Pre‐hospital emergency medicine (PHEM) involves provision of immediate medical care to critically ill and injured patients, across all age ranges, often in environments that may be remote and are not only physically challenging but also limited in terms of time and resources. PHEM is now a GMC‐recognised subspecialty of anaesthesia or emergency medicine and the first recognised training program in the UK commenced in August 2012. This article discusses subspeciality development in PHEM, the competency based framework for training in PHEM, and the provision of pre‐hospital emergency anaesthesia.